Reliability design of relief groove for torque shaft of shearer. (January 2020) - Gao, Hongbin; Zhang, Qianqian
On cutting coal, the cutting resistance of a shearer may change suddenly due to uneven coal quality. It can lead to sudden acceleration of the cutting motor, deceleration, overload shutdown, and even burnout of the motor. We studied the dynamic, static, and working characteristics of the torque shaft of a typical shearer to ensure that the torque shaft of the cutting unit can transfer the torque from the cutting motor to the gear reducer in the rocker under rated conditions and be turned off immediately to protect the motor in case of overload. A method of radial size design of the relief groove of torque shaft based on combining positive, reverse reliability with unloading coefficient has been presented, and the flow chart using this design method has been provided. The positive and reverse reliability torsional test of strength of the experimental torque shafts without relief grooves using three different materials and the measurement test of unloading coefficient of various types of relief grooves were performed. The experimental results obtained through our investigation achieve and even surpass the design purpose. More importantly, to serve the industry it is designed for, the torque shaft designed using this method has high reliability.